RETRACTED: Modelling the dynamics of the force interaction between the prosthetic sleeve and the patient's hand - Lukyanov Evgeny; Khashev Denis; Lysenko Aleksey (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001